AN ENGLISH TEACHER’S PERCEPTION ON THE REMOVAL OF THE ENGLISH SUBJECT AT ELEMENTARY SCHOOL - Elda Elda Nurlatifah; Arham Mauriyat (PROJECT (Professional Journal of English Education), 2020)
The removal of English in elementary schools in the 2013 Curriculum has surprised education practitioners in Indonesia, whereas English is an international language that needs to be taught to all students throughout Indonesia. The purpose of this study is to analyze an English teacher’s perception on the removal of the English subject at elementary school in Cipatat. This research used a qualitative case study approach that focuses on individual experience through an interview. The results of this research explained that the removal of English made students not enthusiastic in learning English, which especially impacted on their lack of knowledge of vocabulary at the next level. Therefore, teachers must give more motivation to students despite their teaching load, and they must be more optimal and creative in teaching with limited time every week. On the other hand, as students in Indonesia tend to lack interest in reading, the removal of English at this level gives them an advantage, which is to make students increase their literacy and love their national language more.